(untitled) (Journal of Educational Sciences, 2019)
In Kazakhstan every year a significant number of students are transferred from one university to another one. In international practice, all types of departures from universities are the object of close attention of researchers, since the ability of a university to retain students until completion of training is considered an important characteristic of its effectiveness. In Kazakhstan, such a study was undertaken for the first time, and therefore the authors identified the basic terminology of this academic field and identified the reasons for student transfers between universities. The study applied a qualitative method, namely the case study of two universities. Respondents for the interviews were selected on the basis of purposeful sampling of students transferred from different universities at different times. Most of these students made the decision to transfer due to academic, financial problems or insufficient level of interaction with staff and teachers of the university, peers. Based on the interviews, the article presents recommendations for universities on how to improve institutional transfer practices. They are connected with statements about the need for university staff to understand the problems of transfer students, strengthen interaction with them, create manuals and handbooks for transfer process, online portals and other support measures. The results of the study can be used by employees and teachers of higher educational institutions for effective interaction with «transfer students» in order to successfully complete their studies. Key words: higher education, student transfer, academic integration, retention.